Roundtable discussion on gender and social inclusion in the energy sector: research findings and stakeholder perspectives - Aryal, Mamata; Karki, Darshan (International Water Management Institute, 2024)
A roundtable discussion organized by IWMI in June 2024 shared results from a NEXUS Gains’ assessment of policy coherence and the implementation gap in gender equality and social inclusion (GESI) policy in the energy sector in Nepal. The interactive event brought together key stakeholders to discuss the relevance and usefulness of the research findings for their areas of work.